No association between resistance mutations, empiric antibiotic, and mortality in ceftriaxone-resistant Escherichia coli and Klebsiella pneumoniae bacteremia - Lye, David Chienboon (2018)
The objective of this study was to correlate resistance mutations of extended spectrum beta-lactamases (ESBL) and AmpC beta-lactamases and virulence factors (VF) with 30-day mortality in patients treated with either piperacillin-tazobactam or carbapenems. A post-hoc analysis on 123 patients with ceftriaxone-resistant Escherichia coli and Klebsiella pneumoniae bacteremia treated empirically with piperacillin-tazobactam and carbapenems was performed. Beta-lactamase resistance mutations and VF were identified by whole genome sequencing (WGS). The primary endpoint was 30-day mortality. Multivariate analyses were performed using logistic regression. WGS showed diverse multilocus sequence types (MLST) in 43 K. pneumoniae strains, while ST131 predominated in E. coli strains (57/80). CTX-M was most commonly detected (76/80 [95%] of E. coli; 39/43 [91%] of K pneumoniae.), followed by OXA (53/80 [66%] of E. coli; 34/43 [79%] of K. pneumoniae). A significant correlation was found between the number of genes encoding third-generation cephalosporin-resistant beta-lactamases and 30-day mortality (p=0.045). The positive association was not significant after controlling for empiric carbapenem, Pitt score 3 and K. pneumoniae (OR 2.43, P=0.073). None of the VF was associated with 30-day mortality. No association was found between 30-day mortality and any ESBL and AmpC beta-lactamases or VF when piperacillin-tazobactam or carbapenems were given. No significant association between 30-day mortality and active empiric therapy was found.